Analisis Pengaruh Net Profit Margin (Npm), Current Ratio (CR) Dan Working Capital Turnover (WCTO) Terhadap Return Saham Pada Perusahaan Sub Sektor Rokok Yang Terdaftar Di Bursa Efek Indonesia (BEI) - IRWATI WATI; NAFISAH NURULRAHMATIAH; ALWI ALWI (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of Net Profit Margin (NPM), Current Ratio (CR), and Working Capital Turnover (WCTO) on stock returns in cigarette sub-sector companies listed on the Indonesia Stock Exchange (IDX). Stock return is an important indicator that reflects the level of profit earned by investors and is therefore influenced by various fundamental factors of a company. This research uses a quantitative approach with descriptive and verificative methods. The data used are secondary data obtained from the annual financial reports of cigarette sub-sector companies listed on the IDX during the 2019–2023 period. The data analysis technique employed is multiple linear regression analysis, including classical assumption tests, partial test (t-test), and simultaneous test (F-test) to examine the research hypotheses. The results indicate that partially, the Net Profit Margin (NPM) variable has a positive and significant effect on stock returns. The Current Ratio (CR) does not have a significant effect on stock returns, while the Working Capital Turnover (WCTO) shows a negative but insignificant effect. Simultaneously, these three variables influence stock returns, although not all are individually significant. These findings suggest that profitability is the primary factor considered by investors in making investment decisions in the cigarette sub-sector, while liquidity and working capital turnover efficiency play a lesser role in influencing stock returns. This research is expected to provide valuable insights for investors, company management, and academics in understanding the financial factors affecting stock returns in this specific industrial sector.